Sparring partners - Grisham, John (Doubleday, 2022)
"Homecoming" takes us back to Ford County, the fictional setting of many of John Grisham's unforgettable stories. Jake Brigance is back, but he's not in the courtroom. He's called upon to help an old friend, Mack Stafford, a former lawyer in Clanton, who three years earlier became a local legend when he stole money from his clients, divorced his wife, filed for bankruptcy, and left his family in the middle of the night, never to be heard from again--until now. Now Mack is back, and he's leaning on his old pals, Jake and Harry Rex, to help him return. His homecoming does not go as planned. In "Strawberry Moon," we meet Cody Wallace, a young death row inmate only three hours away from execution. His lawyers can't save him, the courts slam the door, and the governor says no to a last-minute request for clemency. As the clock winds down, Cody has one final request. The "Sparring Partners" are the Malloy brothers, Kirk and Rusty, two successful young lawyers who inherited a once prosperous firm when its founder, their father, was sent to prison. Kirk and Rusty loathe each other, and speak to each other only when necessary. As the firm disintegrates, the resulting fiasco falls into the lap of Diantha Bradshaw, the only person the partners trust. Can she save the Malloys, or does she take a stand for the first time in her career and try to save herself? By turns suspenseful, hilarious, powerful, and moving, these are three of the greatest stories John Grisham has ever told.